Аналіз використання системи управління CRM - Волощенко, П. В. (ХНУРЕ, 2019)
Customer Relationship Management (CRM) is a relationship management system clinging to. Technology focused on optimizing mutual owner-owned organization with organization. "In essence, it can be made easier and automate the business processes of the company, the robotic organization, as effective as possible.